Pseudopotential study of the thermodynamic characteristics of supercooled Mg and Zn melts; Soviet Physics Journal; Vol. 27, iss. 4 - Zol'nikov K. P.; Psakhie S. G. Sergey Grigorievich; · Landa A. I.; Panin V. E. Viktor Evgenyevich (1979, 1979)
Title screen